Computing technology in international development: who, what, where, when, why and how? - Kam, Matthew; Dray, Susan; Toyama, Kentaro; Marsden, Gary; Parikh, Tapan; Cutrell, Ed (CHI EA '10: Proceedings of the 28th of the international conference extended abstracts on Human factors in computing systems, 2010)
Building on the successes of prior workshops at CHI and other HCI conferences on computing in international development, we propose a panel to engage with the broader CHI community. Topics to be discussed include why international development is important to HCI as a discipline, and how CHI researchers and practitioners who are not already involved in international development can contribute.